A 2-Week Course of Enteral Treatment with a Very Low-Calorie Protein-Based Formula for the Management of Severe Obesity - Giuseppe Castaldo; Luigi Monaco; Laura Castaldo; Paolo Sorrentino (International Journal of Endocrinology)
Background. Multiple weight loss failures among obese patients suggest the design of new therapeutic strategies. We investigated the role of 2-week course of enteral treatment with a very low-calorie protein-based formula in the management of severe obesity. Methods. We evaluated the feasibility, safety, and efficacy of 2-week continuous administration of a protein-based formula (1.2 g/kg of ideal body weight/day) by nasogastric tube in severely obese adults (body mass index (BMI) ≥ 40 kg/m2). Results. In total, 364 patients (59% women; BMI = 46.6±7.2 kg/m2) were recruited. The intervention was discontinued within 48 hours in 26 patients, due to nasogastric tube intolerance. No serious adverse events occurred. During the first and the second week, 65% and 80% patients, respectively, reported no side effects. All biochemical safety parameters were affected by the intervention, particularly uric acid (+45%) and aminotransferases (+48%). In the other cases the change was negligible. We observed significant weight loss (5.7±2.3%) and improvement in blood pressure and glucose and lipid metabolism parameters (P<0.001). Conclusions. A 2-week course of enteral treatment with a very low-calorie protein-based formula appeared a feasible, likely safe, and efficacious therapeutic option to be considered for inclusion into a composite weight loss program for the management of severe obesity. This trial is registered with ClinicalTrials.gov Identifier: NCT01965990.